The effect of a glucagon-like peptide-1 receptor agonist on glucose tolerance in women with previous gestational diabetes mellitus: protocol for an investigator-initiated, randomised, placebo-controlled, double-blinded, parallel intervention trial. Issue 10 (30th October 2013) - Foghsgaard, Signe; Vedtofte, Louise; Mathiesen, Elisabeth R; Svare, Jens A; Gluud, Lise L; Holst, Jens J; Damm, Peter; Knop, Filip K; Vilsbøll, Tina
Abstract : Introduction: Pregnancy is associated with decreased insulin sensitivity, which is usually overcome by a compensatory increase in insulin secretion. Some pregnant women are not able to increase their insulin secretion sufficiently, and consequently develop gestational diabetes mellitus (GDM). The disease normally disappears after delivery. Nevertheless, women with previous GDM have a high risk of developing type 2 diabetes (T2D) later in life. We aim to investigate the early development of T2D in women with previous GDM and to evaluate whether treatment with the glucagon-like peptide-1 receptor (GLP-1R) agonist, liraglutide, may modify their risk of developing T2D. Methods and analyses: 100 women with previous GDM will be randomised to either liraglutide or placebo treatment for 1 year (blinded) with an open-label extension for another 4 years. Additionally, 15 women without previous GDM will constitute a baseline control group. Women will be tested with an oral glucose tolerance test (primary endpoint: area under the curve for plasma glucose) and an isoglycaemic intravenous glucose infusion at baseline, after 1 year and after 5 years. Additional evaluations include a glucagon test, dual-energy X-ray absorptiometry, imaging of the liver (ultrasound elastography and fibroscanning), an ad libitum meal for food intake evaluation and questionnaires related to appetite, quality of life and alcohol consumption habits. Ethics and dissemination: The protocol has been approved by the Danish Medicines Agency, the Scientific-Ethical Committee of the Capital Region of Denmark, and the Danish Data Protection Agency and will be carried out under the surveillance and guidance of the GCP unit at Copenhagen University Hospital Bispebjerg in compliance with the ICH-GCP guidelines and in accordance with the Helsinki Declaration. Positive, negative and inconclusive results will be published at scientific conferences and as one or more scientific manuscripts in peer-reviewed journals. Registrations: The trial is registered at https://eudract.ema.europa.eu (2012-001371-37) and http://www.clinicaltrials.gov (NCT01795248 ).